1968
DOI: 10.1071/bi9680569
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Kinetin on the Translocation if 14C-Labelled Photosynthate in Citrus

Abstract: This study indicates that the application of kinetin to a recently formed fruit enhances its ability to import photosynthetic assimilates. Cytokinins are known to influence .the transport of plant metabolites (Letham 1967), and in the case of vine shoots Shindy and Weaver (1967) have recently demonstrated an effect of the kinin 6-(benzylamino)-9-(2-tetrahydropyranyl)-9H-purine on the translocation of 14C_ labelled assimilates. The present paper reports an effect of kinetin (6-furfurylaminopurine) on the accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 5 publications
4
4
0
Order By: Relevance
“…The decrease of both trans zeatin and zeatin riboside in the roots suggests the possibility that CO2 treatments may cause a conversion of trans zeatin to zeatin riboside and, in turn, also enhance the translocation of zeatin riboside to the top of the plant. This is consistent with the increase in dry matter content resulting from CO2 applications previously noted (1) and is supported by previous evidence that cytokinins are mobilizing agents of stored reserves (6,9,17). This is also in agreement with the findings of Meidner ( 11) who showed an increase in photosynthesis with applications of cytokinins.…”
Section: Resultssupporting
confidence: 79%
“…The decrease of both trans zeatin and zeatin riboside in the roots suggests the possibility that CO2 treatments may cause a conversion of trans zeatin to zeatin riboside and, in turn, also enhance the translocation of zeatin riboside to the top of the plant. This is consistent with the increase in dry matter content resulting from CO2 applications previously noted (1) and is supported by previous evidence that cytokinins are mobilizing agents of stored reserves (6,9,17). This is also in agreement with the findings of Meidner ( 11) who showed an increase in photosynthesis with applications of cytokinins.…”
Section: Resultssupporting
confidence: 79%
“…2), indicating that BA has a general effect on the movement of different types of compounds. Our results support the hypothesis that transport of photosynthetically assimilated "CO2 is controlled by plant hormones (3,10,17,22,29). Benzyladenine has been shown to increase the movement of "C-assimilates into fruit clusters (39), shoot tips (32,33), and leaves (34) of grapevines.…”
Section: Discussionsupporting
confidence: 79%
“…Kriedemann et al (17) and Saito and Kasai (30) found that rapidly expanding grape leaves, such as the apical leaves used in our experiments, incorporate the greatest proportion of "CO, into organic acids, with smaller amounts going into amino acids and sugars. Fully expanded leaves, in contrast, incorporate "CO2 mostly into sugars (7).…”
Section: Discussionmentioning
confidence: 93%
“…Little such work has been done with flowers or fruits. However, Kriedemann (9) recently has shown that the application of kinetin to a voung fruit of orange cv. Washington Navel enhances its ability to import photosvnthetic assimilates.…”
Section: Discussionmentioning
confidence: 99%